2017
DOI: 10.1038/s41598-017-11674-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Endometrial Sodium Glucose Cotransporter SGLT1 is Detrimental to Embryo Survival and Fetal Growth in Pregnancy

Abstract: Embryo implantation requires a hospitable uterine environment. A key metabolic change that occurs during the peri-implantation period, and throughout early pregnancy, is the rise in endometrial glycogen content. Glycogen accumulation requires prior cellular uptake of glucose. Here we show that both human and murine endometrial epithelial cells express the high affinity Na+-coupled glucose carrier SGLT1. Ussing chamber experiments revealed electrogenic glucose transport across the endometrium in wild type (Slc5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…In addition, downregulation of SGLT1 in small intestine via inhibition of NHE3 may confer advantages in contrast to direct inhibition of SGLT1. This is suggested by recent literature, showing that absorption of SGLT1 inhibitors into the systemic circulation exerts its action on the heart, liver, lung, brain, and T‐lymphocytes, as well as the uterus, thereby possibly inducing serious side effects through localized SGLT1 inhibition. Moreover, SGLT1 inhibitors may compromise host defence against infection, as indicated by excessive bacterial loads in the liver, spleen, kidney and lung after Listeria monocytogenes infection, subsequently resulting in death of all SGLT1‐deficient mice .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, downregulation of SGLT1 in small intestine via inhibition of NHE3 may confer advantages in contrast to direct inhibition of SGLT1. This is suggested by recent literature, showing that absorption of SGLT1 inhibitors into the systemic circulation exerts its action on the heart, liver, lung, brain, and T‐lymphocytes, as well as the uterus, thereby possibly inducing serious side effects through localized SGLT1 inhibition. Moreover, SGLT1 inhibitors may compromise host defence against infection, as indicated by excessive bacterial loads in the liver, spleen, kidney and lung after Listeria monocytogenes infection, subsequently resulting in death of all SGLT1‐deficient mice .…”
Section: Discussionmentioning
confidence: 87%
“…In addition, downregulation of SGLT1 in small intestine via inhibition of NHE3 may confer advantages in contrast to direct inhibition of SGLT1. This is suggested by recent literature, showing that absorption of SGLT1 inhibitors into the systemic circulation exerts its action on the heart, liver, lung, brain, and Tlymphocytes, 27 as well as the uterus, 35 thereby possibly inducing serious side effects through localized SGLT1 inhibition. Moreover, SGLT1…”
Section: Discussionmentioning
confidence: 89%
“…Lack of Sglt1 compromises endometrial glycogen storage, resulting in reduced litter size and low birth weight in mice (Salker et al . ). The endometrial expression of interferon alpha and beta receptor subunit 1 ( IFNAR1 ) was influenced by different synchronization treatments, which could affect uterine response to pregnancy (Ruiz‐Gonzalez et al .…”
Section: Discussionmentioning
confidence: 97%
“…The limitation of the study however was the use of immunohistochemistry, which is a semi-quantitative method. Further research is needed to confirm whether SGLT1 has a role in the development and progression of ovarian cancer, especially because Salker et al (54) has recently reported SGLT1 activity in normal ovary tissue (human endometrium), where it controlled glycogen accumulation essential for embryo implantation.…”
Section: Sglt1 In Ovarian Cancermentioning
confidence: 99%